Studies on mosquitoes (Diptera: Culicidae) and anthropic environment: 7- Behaviour of adults Nyssorhynchus anophelines with special reference to Anopheles albitarsis s.l. in South-Eastern Brazil - Oswaldo Paulo Forattini; Iná Kakitani; Eduardo Massad; Daniel Marucci (Universidade de São Paulo, 1995)
Results obtained with catches performed at several sites of the Ribeira Valley, SP (Brazil) are reported. Collections with Shannon type traps showed a concentration of An.albitarsis s.l. in the Experimental Farm of Pariquera-Açu County, associated with the development of irrigated rice cultivation. Two species of the complex, named A and B, were recognized. Species B predominated in the samples. Indoor and outdoor crepuscular human bait captures were performed a the domiciliary environment. The two species showed a generally low William's media valve of 0.2, the highest value obtained was 1.6. No differences were found between indoor and outdoor behaviours between the two species of the complex. Relatam-se os resultados obtidos com coletas levadas a efeito em áreas do Vale do Ribeira, SP (Brasil) e mediante o emprego de armadilhas tipo Shannon. As evidências obtidas mostraram clara associação com o cultivo de arroz irrigado na Fazenda Experimental de Pariquera-Açu. Tudo leva a crer que ali ocorra concentração populacional desse complexo na qual pôde-se diferenciar duas espécies, designadas como A e B. A espécie B predominou francamente em todas as coletas. No ambiente domiciliar foi empregada a isca humana nas coletas efetuadas regularmente no intra e no peridomicílio. Em ambas situações foram encontradas as duas espécies, com baixo valor geral da média de Williams correspondente a 0,2. Considerando-se separadamente os resultados mensais, pôde-se obter valor máximo de 1,6. Não foi possível detectar qualquer diferença entre os dois ambientes, no que concerne à freqüência de ambas as espécies do complexo.